PENGARUH PERTUMBUHAN DANA PIHAK KETIGA, PERTUMBUHAN KREDIT, RISIKO KREDIT DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ni Kadek Sulistiawati; I Wayan Sukadana; I Wayan Widnyana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
The purpose of this study was to determine and analyze the effect of growth in third party funds, credit growth, credit risk and liquidity on profitability in banking sub-sector companies listed_in Indonesia Stock Exchange. The type_of data_in this research is quantitative and_qualitative data. Sources of data in this study using secondary data. This study used purposive sampling, and the data_collection method_used non-participant observation and the data analysis_technique used_multiple linear regression tests